Finite Volume Method for the Launch Safety of Energetic Materials - Yanchun Yu; Han Yan; Weidong Chen; Jingxin Ma (Shock and Vibration)
It is important to examine the ignition of energetic materials for launch safety. Given that there is a paucity of experimental tests, numerical simulations are important for analysing energetic materials. A computer program based on the finite volume method and viscoelastic statistical crack mechanics model is developed to study the ignition of energetic materials. The trends of temperature and stress of energetic materials subjected to projectile base pressure are studied by numerical examples. The results are compared with those in an extant study, which verified the correctness of the proposed method. Additionally, the relationships between the temperature increase and nonimpact ignition of energetic materials were analysed. The results show that when the temperature at the bottom of the explosive rises to a certain value, it will cause the explosive to ignite. This research has significance to the study of the base gap of explosives, and it provides a reference for launch safety evaluation of energetic materials.